Approximation by Lupas-Type Operators and Szász-Mirakyan-Type Operators - Hee Sun Jung; Ryozi Sakai (Journal of Applied Mathematics)
Lupas-type operators and Szász-Mirakyan-type operators are the modifications of Bernstein polynomials to infinite intervals. In this paper, we investigate the convergence of Lupas-type operators and Szász-Mirakyan-type operators on [0,∞).